Perancangan Sistem Pakar Diagnosis Penyakit Pada Hewan Peliharaan Anjing Berbasis Web Menggunakan Metode Forward Chaining - Lumbantoruan, Angelina Romauli; Niska, Debi Yandra (Teknik Komputer Politeknik Negeri Sriwijaya, 2024)
Pets, including dogs, play a crucial role in human life and have become an integral part of modern households. The intelligence and loyalty of dogs are some of the reasons why they are kept as pets and valued as excellent protectors of homes. With the increasing population of dogs, there is a significant need for suitable living spaces and proper care for the. Although many pet owners seek help form veterinarians when their pets experience health issues, limitations in time and expenses often become hindrances. As technology advances, expert systems have emerged as promising solutions for diagnosing diseases ini pet animals. This research implements the Forward Chaining method for reasoning and the Certainty Factor for measuring the certainty value in the diagnosis process. The system is expected to assit all pet owners, especially those with dogs, ini identifying potential health issues that may arise in their pets. Additionally, the system can aid experts in providing preliminary diagnoses. Through testing conducted, it was found that 30 data showed consistent agreement between the expert’s assessments dan the system’s results.